Minnie and Moo and the Potato from Planet X - Cazet, Denys (New York : HarperCollins, 2002)
Minnie and Moo come to the aid of a visitor from outer space.
Keywords: Children's stories; Extraterrestrial beings -- Fiction; Cows -- Fiction; Early Chapter book; Early Chapter book